Transverse flux machines as an alternative to radial flux machines in an in‐wheel motor. Issue 17 (31st May 2019) - Martinez‐Ocaña, Iago; Baker, Nick J.; Mecrow, Barrie C.; Hilton, Chris; Brockway, Simon
Abstract : This paper considers the use of transverse flux machines (TFMs) as an alternative to radial flux machines (RFMs) in an in‐wheel application for an electric vehicle. The base motor is an existing outer rotor surface‐mounted permanent magnet machine with fractional slot concentrated windings and liquid cooling. Two topologies of TFM are compared against this base machine. The first topology is a mutual flux path (TFM‐MP), while the second is a claw pole machine (TFM‐CP). First, the proposed TFM topologies are studied using FEA to understand the torque capability of both topologies. Second, a comparison between two different pole numbers of each topology is compared with the performance of the benchmarking machine (BMM). The machines will be compared in terms of torque density, losses, efficiency, and power factor (PF). Finally, it is presented as a comparison on the torque capabilities when constraining the magnet mass. It is shown that the TFMs selected can deliver higher torques than the base motor during continuous operation, but have failed to deliver the required overload torque. Furthermore, low PF and low efficiency make these machines unsuitable for the application of this in‐wheel traction motor.